Modeling the Thermal Behavior of the Viscoelastic Properties of Asphalt Concrete - Saad I. Sarsam (Britain International for Academic Research (BIAR) Publisher, 2022)
The viscoelastic properties of asphalt concrete are susceptible to the variation in the pavement temperature. In the present work, asphalt concrete beam specimens were prepared at optimum binder content and tested under repeated flexural stresses for fatigue life. Three testing temperature were implemented (5, 20, and 30) ℃. The variation in the phase angle, dissipated energy, flexural stiffness, and permanent deformation due to the testing temperatures were monitored and modeled. It was concluded that the viscoelastic properties of asphalt concrete are highly sensitive to the variation in testing temperature. The phase angle and the permanent deformation increases sharply as the testing temperature rises. However, the dissipated energy and the flexural stiffness declines as the testing temperature rise. Mathematical models were obtained which can be implemented in identifying the thermal behavior of the viscoelastic properties of asphalt concrete.